Biorefining of legume and grass biomasses: technological properties and bioactivities of the green juice - Pap, Nora; Granato, Daniel; Järvenpää, Eila; Tienaho, Jenni; Marnila, Pertti; Hellström, Jarkko; Pihlava, Juha-Matti; Franco, Marcia; Stefański, Tomasz; Rinne, Marketta (Elsevier, 2024)
Five legume species (fodder galega, green pea, faba bean, red clover, and white clover) and one grass (timothy) grown under field conditions were investigated as potential future foods. Technological characteristics, such as emulsifying and foaming properties and nitrogen solubility indices, were determined from the green juices pressed from the whole plants. Secondly, the juices were evaluated for their antioxidative, antibacterial and anti-inflammatory properties. Faba bean green juice showed the highest emulsion stability and capacity, 66.0 ± 3.3 % and 18.0 ± 2.7 g/mg respectively, and second highest emulsion activity (58.4 ± 0.92 %). Considering the foaming properties, the highest activity was shown by white clover (433 ± 0.0 %) and green pea juices (411 ± 19.2 %). At the same time, the foam stability was remarkable for green pea juice (1078 ± 181.9 min) when compared to the other juices studied. The juices showed nitrogen solubility indices of about 50 % at pH 8, which were rather similar to those shown for the seeds of the same species in the literature. The antioxidant activities correlated with the total phenolic content. The highest antioxidant activity was shown by faba bean green juice both in the oxygen radical absorbance capacity (ORAC) and the ferric reducing antioxidant power (FRAP) method. In addition, a weak positive correlation was observed between the total phenolic content and the antibacterial properties using Escherichia coli and Staphylococcus aureus strains, although mainly in the case of the latter strain, high inhibition readings were observed for all other plants than white clover. All juices showed some anti-inflammatory activity on human monocyte activation: the faba bean and red clover were the most efficient materials (IC50 concentrations 49 ± 41 and 206 ± 68 mg/L, respectively).- These results suggest that the green juices tested may provide novel health-promoting food and feed ingredients in the future.
Keywords: green biorefinery; phenolic acids; flavonoids; antioxidant activity; antibacterial activity; anti inflammatory activity; technological properties; Galega orientalis; Pisum sativum; Vicia faba; Trifolium pratense; Trifolium repens; Phleum pratense